Rekayasa : jurnal penerapan teknologi dan pembelajaran - Universitas Negeri Semarang. Lembaga Pengabdian Kepada Masyarakat
Study on implementation of technological innovations in home industries and implementation of educational technology in Indonesia.
Keywords: Home-based businesses : Technological innovations : Indonesia : Periodicals; Educational technology : Indonesia : Periodicals; Educational technology; Home-based businesses : Technological innovations; Indonesia